The polymicrobial nature of the oral cavity and claws of cats diagnosed by mass spectrometry and next-generation sequencing - Portilho, Fábio V.R. [UNESP]; Nóbrega, Juliano [UNESP]; de Almeida, Beatriz O. [UNESP]; Bello, Thaís S. [UNESP]; Paz, Patrik J.L. [UNESP]; Oliveira, Alana L. [UNESP]; Bosco, Sandra M.G. [UNESP]; Rall, Vera L.M. [UNESP]; Giuffrida, Rogério; Ribeiro, Márcio G. [UNESP] (Elsevier, 2024)
Close contact between cats and humans increases the risk of transmission of zoonotic pathogens, through bites and scratches due to the complexity of microorganisms in the oral and nail microbiotas of felines. This study investigated the presence of bacteria and fungi in the oral cavity and claws of 100 apparently healthy cats using conventional and selective microbiological culture media, and next-generation sequencing (NGS) and mass spectrometry (MALDI-TOF MS). Furthermore, antimicrobial susceptibility testing of bacteria isolates was performed by disc diffusion method. In total, 671 bacteria and 33 yeasts were identified by MALDI-TOF MS. Neisseria animaloris (10.8 %), Staphylococcus felis (8.5 %), and Pasteurella multocida (7 %) were the most prevalent bacteria in oral cavity samples (n = 343), while the most common yeast (n = 19) was Candida albicans (68.4 %). Staphylococcus pettenkoferi (13.4 %), Staphylococcus felis (6.4 %), and Staphylococcus simulans (5.8 %) were the prevalent bacteria identified in the claw samples (n = 328), while Rhodotorula mucilaginosa (57.2 %) was the most common yeast (n = 14). NGS predominantly identified the genera Moraxella, Neisseria, Pasteurella, and Fusobacterium in oral cavity samples, whereas enterobacteria and staphylococci were prevalent in nail bed samples. In addition, the genera Capnocytophaga and Bartonella were identified, which have been described in serious human infections secondary to feline aggressions. Levofloxacin, marbofloxacin, and amoxicillin/clavulanic acid were the most effective drugs against the main groups of bacteria identified. Multidrug resistance was observed in 17 % of the bacterial isolates. Furthermore, three staphylococci harboring the methicillin resistance gene mecA were identified. We highlight the complexity of microorganisms inhabiting the oral/claw microbiotas of cats, the high resistance rate of the isolates to conventional antimicrobial agents, and the zoonotic risk of aggressions caused by bites and scratches from domestic cats.
Keywords: 16S rRNA; Feline oral and claw microbiota; MALDI TOF-MS; mecA gene; Microbiome